Bioengineer mesenchymal stem cell for treatment of glioma by IL‐12 mediated microenvironment reprogramming and nCD47‐SLAMF7 mediated phagocytosis regulation of macrophages - Man Li; Lisen Lu; Qungen Xiao; Ali Abdi Maalim; Bin Nie; Yanchao Liu; Ulf D. Kahlert; Kai Shu; Ting Lei; Mingxin Zhu (Exploration)
Abstract High expression of cellular self‐activated immunosuppressive molecules and extensive infiltration of suppressive immune cells in the tumor microenvironment are the main factors contributing to glioma's resistance to immunotherapy. Nonetheless, technology to modify the expression of glioma cellular self‐molecules through gene editing requires further development. This project advances cell therapy strategies to reverse the immunosuppressive microenvironment of glioma (TIME). Bone marrow‐derived mesenchymal stem cells (MSCs) are engineered to express bioactive proteins and demonstrate tumor‐homing characteristics upon activation by TGF‐β. These MSCs are designed to secrete the anti‐tumor immune cytokine IL‐12 and the nCD47‐SLAMF7 fusion protein, which regulates T‐cell activity and macrophage phagocytosis. The engineered MSCs are then injected in situ into the glioma site, circumventing the blood‐brain barrier to deliver high local concentrations of bioactive proteins. This approach aims to enhance the M1 polarization of infiltrating macrophages, stimulate macrophage‐mediated tumor cell phagocytosis, activate antigen‐presenting cells, and promote effector CD8+ T cell infiltration, effectively controlling glioma. Additionally, the engineered MSCs may serve as a universal treatment for other tumors that express TGF‐β at high levels. This study proposes a novel treatment strategy for the clinical management of glioma patients.